Supercondutividade e Magnetismo no Sistema y(ni,t=mn,co,fe)2b2c - dos Santos, Cláudia Lange; da Silva, Celso A. M. A. M.; Gomes, Affonso A. (Ciência e Natura, 2007)
SUPERCONDUTIVIDADE E MAGNETISMO NO SISTEMA Y(NI,T=MN,CO,FE)2B2C